Analisis Kinerja Keuangan Pemerintah Daerah: Studi Komparasi Propinsi Jawa Tengah dan Kalimantan Selatan - Sri Suranta; Halim Dedy Perdana; M. Syafiqurrahman (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to determine the Financial Performance of Regional Government both District Government and City Government between Central Java Province (West Indonesia Region) and South Kalimantan (Central Indonesia Region) after the enactment of regional autonomy. This study emphasizes the exist or no of differences in local government financial performance outlined by the dimensions: Regional Financial Independence, Fiscal Decentralization, Efficiency and Effectiveness of Original Income between Central Java and South Kalimantan provinces. This study uses a sample of District and City Government Work Units in Central Java and South Kalimantan Provinces. The data used is obtained from Local Government Financial Report. The results of this study indicate differences in Financial Performance in terms of Regional Financial Independence, fiscal decentralization and efficiency in Central Java and South Kalimantan Provinces. Meanwhile, the ratio of effectiveness showed no difference between the two regions. Keywords: Local Government Financial Performance, Central Java, South Kalimantan